(When) Are Dynamic Capabilities Routine? A Mixed-Methods Configurational Analysis - Hendrik Wilhelm; Indre Maurer; Mark Ebers (Journal of Management Studies, 2021)
Dynamic capabilities research is hampered by a theoretical divide. This divide concerns, first, whether dynamic capabilities are routine or not, and, second, whether firms in dynamic environments deploy routine or non-routine dynamic capabilities. The divide is significant for theory, as it pertains to the conceptualization and boundary conditions of dynamic capabilities. The present study offers a pathway for reconciling the divide by overcoming the bifurcation of routine and non-routine dynamic capabilities that dominates the debate. Conceptually, we relax extant assumptions on dynamic capability routineness by allowing for the possibility that dynamic capabilities may vary in dimensions of their routineness (i.e., the frequency and structuring of dynamic capability activities). Findings of a fuzzy-set Qualitative Comparative Analysis of 103 firms operating in more and in less dynamic environments reveal four configurations of dynamic capabilities (i.e., Experimental, Adaptive, Programmed, and Analytical) that fundamentally differ in their routineness. Moreover, we find that environmental dynamism does not constitute a boundary condition for the routineness of dynamic capabilities. In-depth analyses of 16 cases suggest that the different dynamic capability configurations we observe depend not only on environmental dynamism but also on distinct intra-firm conditions (i.e., organizational learning orientations and resource allocations). As its main contribution, this study offers a configurational framework explaining heterogeneity in the routineness of dynamic capabilities that advances our understanding of the nature and boundary conditions of dynamic capabilities.
Keywords: 650; configurational perspective; dynamic capabilities; fsQCA; mixed methods